Somatotype characteristics of elite young athletes from the republic of kosovo - Kastrati, A.; Gashi, N.; Georgiev, G.; Gontarev, S. (SportMont, 2022)
A large number of published studies have established the somatotype characteristics of athletes from different sports. The research goal is to establish and compare the anthropometric characteristics, body composition, and somatotype components of Kosovo`s young elite athletes. The research was conducted on 255 young athletes aged 18, divided into 92 footballers, 83 basket players, and 80 handball players. The obtained results show numerous relations and differences between the tested young athletes. The research results suggest that footballers are shorter and lighter than basketball and handball players; have lower BMI than handball players. Handball players are shorter than basketball players, and have greater BMI than basketball players and footballers. Footballers, compared to handball players have a greater bone-component and less fat-component percentage. Basketball players possess greater bone-component percentage values than handball players. Footballers have a dominant mesomorph component. Their somatotype category is balanced mesomorph. Handball players are established to have a common mesomorph athletic type with a characteristic skeleton`s longitudinal dimension. The ectomorph body type is dominant in basketball players - a mesomorph- body type with a characteristic skeleton`s longitudinal dimension and balanced correlation between the bone and muscle tissue. Therefore, these findings may give coaches from the region better working knowledge and suggest to them to follow recent selection process methods and be more diligent during the process of talent scouting.